2003
DOI: 10.1007/s10295-002-0018-9
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for laboratory testing of crude-oil bioremediation products in freshwater conditions

Abstract: In 1993, the Environmental Protection Agency, National Risk Management Research Laboratory (EPA, NRMRL), with the National Environmental Technology Application Center (NETAC), developed a protocol for evaluation of bioremediation products in marine environments [18]. The marine protocol was adapted for application in freshwater environments by using a chemically defined medium and an oil-degrading consortium as a positive control. Four products were tested using the modified protocol: two with nutrients and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The limited glucose concentration is essential to avoid catabolite repression. Aeration plays an important role in oil bioremediation and is considered a rate limiting factor in the biodegradation of marine oil spills where, oxygen is necessary for initial breakdown of hydrocarbon and subsequent reactions (Haines et al, 2003). The presence of phosphate plays a critical role and its inadequate supply may result in slowing the rate of biodegradation (Haines et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The limited glucose concentration is essential to avoid catabolite repression. Aeration plays an important role in oil bioremediation and is considered a rate limiting factor in the biodegradation of marine oil spills where, oxygen is necessary for initial breakdown of hydrocarbon and subsequent reactions (Haines et al, 2003). The presence of phosphate plays a critical role and its inadequate supply may result in slowing the rate of biodegradation (Haines et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In previous work conducted by our laboratory, Haines et al [10] proposed a freshwater protocol for testing bioremediation products to include performance targets, a positive control, and a defined nutrient formula. Four products were tested and two were able to degrade >90% alkane and >60% aromatic hydrocarbons within 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the MPN procedure was used as described [20] for saltwater and modified for fresh water by using SFW medium rather than GP2 [10]. For both alkane-and PAH-degrader enumeration, the MPN was calculated using a computerized enumeration program [11].…”
Section: Most Probable Number Analysismentioning
confidence: 99%
“…Alkanes of intermediates chain length (C 10 -C 24 ) are often degraded immediately, while long chain alkanes are resistant to microbial degradation (Ijaha & Antaib 2003). According to Haines et al (2003) the decline in bacterial growth upon increased oil concentration was due to oxygen scarcity. The result also showed that extension of incubation period (336 h) did not increase in TPH degradation.…”
Section: Results and Discussion Effect Of Crude Oil Concentration -Inmentioning
confidence: 99%